Alkane isomerization over sulfated zirconia solid acid system. (10th January 2020) - Wang, Pengzhao; Yue, Yuanyuan; Wang, Tinghai; Bao, Xiaojun
Summary: Sulfated zirconia (SZ) and its modified versions attract great interest in recent years, because of their promising potential in n ‐alkane isomerization. The oxidative and protonation routes are active and interactional in n ‐alkane activation over SZ catalysts. The bimolecular reaction becomes dominant with increasing the density of active sites on SZ surface and decreasing the carbon chain of feed. Pentane and hexane are mainly isomerized by protonated cyclopropane mechanism, while which is thermodynamically unflavored for n ‐butane isomerization. The deactivation of SZ catalysts is primarily caused by the loss of superacidity and oxidizing ability, resulted from the structure changes of sulfate species. Several strategies for improving the activity of SZ are reviewed. The intrinsic structure‐reactivity relationship of SZ catalysts in alkane isomerization is updated to illuminate the prerequisite for the highly active catalysts and the mechanism of active sites formation. The applications of Pt/SZ in fixed‐bed and unmodified SZ in circulating fluidizing bed in light alkanes isomerization are compared with the conventional technologies based on the chlorinated alumina catalysts. Finally, the future study of SZ catalysts is outlooked from the academic investigations to the industrial applications. Abstract : The research on sulfated zirconia is ascendant in academic and applied prospects inalkane isomerization. This paper reviews the reaction and deactivation mechanismof sulfated zirconia and its modified versions in n‐alkane isomerization. We share our ideas with researchers in thefuture study for sulfated zirconia catalysts and their catalysis in n‐alkane isomerization.